The Influence of Problem Solving Model Toward Students’ Critical Thinking Skills - Nindya Ananda Latifa; Heffi Alberida (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2019)
The aims of this study was to find whether there was an influence of the Problem Solving Model towards critical thinking skills of students of grade XI in SMAN 9 Padang. A Quasi Experiment method with The Post-test Control Group Only Design was used in this study. Students were grouped in an experimental group (Problem Solving model) and a control group (Direct intruction). The data from a test were analyzed using t-test with a=0,05. The findings showed that there was a significant difference of critical thinking skills enhancement in experimental group than the control group.